Jews and Palestinians in the Late Ottoman Era, 1908-1914. - Fishman, Louis A.
1 online resource (240 pages)
Keywords: Uncovering a history buried by different nationalist narratives (Jewish, Israeli, Arab and Palestinian) this book looks at how the late Ottoman era set the stage for the on-going Palestinian-Israeli conflict.